Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1159/000013518
|View full text |Cite
|
Sign up to set email alerts
|

Renal Reabsorption of Phosphate in Children with Sickle Cell Anemia

Abstract: It has previously been reported that in adult patients with sickle-cell anemia the serum phosphate value and the maximum tubular reabsorption of phosphate per liter of glomerular filtrate (TmP/GFR) were significantly higher than in normal controls. This does not appear to have been studied in children with sickle cell anemia (young sicklers) and this prompted us to assess renal phosphate reabsorption in this group of patients. We looked at serum phosphate level and calculated renal phosphate reabsorption (TP/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…This finding agree with previous study conducted by Nnadi et al [25].The mean of serum phosphorus concentration showed a non-significant decrease (P = 0.547) when compared with the control group(table -2), this agree with the previous study of Al harbi et al [27], Nnadi et al [25],and this is in contrast with the study conducted by Oladipo et al [26],who reported high level in adult and children .The study showed no significant difference in mean serum Ck level in male when compared to female with (P = 0.090), also there is no significant difference in mean serum phosphorus in male when compared to female (P = The study also revealed significantly decrease in serum CK (P = 0.006) in patients used hydroxyurea when compare with the patients not used hydroxyurea. While serum phosphorus showed no significant difference (P = 0.078) between the patients used hydroxyurea and not used hydroxyurea.…”
Section: Discussionsupporting
confidence: 93%
“…This finding agree with previous study conducted by Nnadi et al [25].The mean of serum phosphorus concentration showed a non-significant decrease (P = 0.547) when compared with the control group(table -2), this agree with the previous study of Al harbi et al [27], Nnadi et al [25],and this is in contrast with the study conducted by Oladipo et al [26],who reported high level in adult and children .The study showed no significant difference in mean serum Ck level in male when compared to female with (P = 0.090), also there is no significant difference in mean serum phosphorus in male when compared to female (P = The study also revealed significantly decrease in serum CK (P = 0.006) in patients used hydroxyurea when compare with the patients not used hydroxyurea. While serum phosphorus showed no significant difference (P = 0.078) between the patients used hydroxyurea and not used hydroxyurea.…”
Section: Discussionsupporting
confidence: 93%
“…This finding agree with previous study conducted by Nnadi et al [25].The mean of serum phosphorus concentration showed a non-significant decrease (P = 0.547) when compared with the control group(table -2), this agree with the previous study of Al harbi et al [27], Nnadi et al [25],and this is in contrast with the study conducted by Oladipo et al [26],who reported high level in adult and children .The study showed no significant difference in mean serum Ck level in male when compared to female with (P = 0.090), also there is no significant difference in mean serum phosphorus in male when compared to female (P = 0.611).The study also revealed significantly decrease in serum CK (P = 0.006) in patients used hydroxyurea when compare with the patients not used hydroxyurea. While serum phosphorus showed no significant difference (P = 0.078) between the patients used hydroxyurea and not used hydroxyurea.…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been reported that in adult patients with sickle-cell anemia the serum phosphate value and the maximum tubular re-absorption of phosphate per liter of glomerular filtrate (TmP/GFR) significantly higher than in normal controls. The lower serum phosphate value and TP/ GFR in younger sicklers seems to be in contrast with the relatively high serum phosphate value and TP/GFR previously reported in adults with sickle cell anemia [18]. In sickle cell anemia the shortened survival of red blood cells presents the liver with an augmented load of bilirubin for hepatic clearance [19].…”
Section: Introductionmentioning
confidence: 84%